2013
DOI: 10.3382/ps.2012-02643
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilization and heat production of embryos from eggs originating from young and old broiler breeder flocks

Abstract: Two experiments were conducted to study the interaction between breeder age and egg size on the energy utilization (experiment 1) and heat production (experiment 2) of broiler embryos. In experiment 1, a total of 4,800 Ross-308 hatching eggs from 2 breeder ages (29 and 53 wk of age, or young and old) and, within each age, 2 egg sizes (57 to 61 g and 66 to 70 g, or small and large) were used. In experiment 2, a total of 240 Ross-308 hatching eggs from 2 breeder flocks at 29 (young) and 53 (old) wk of age, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 22 publications
5
38
0
Order By: Relevance
“…The results of chick weight with or without yolk sac corroborate the findings of Rocha et al (2008) and Nangsuay et al (2013), who did not observe any influence of age of broiler breeders on the weight of the yolk residue of one-day-old chicks. However, results differ from those obtained by Riccardi et al (2009), who studied the weight of the yolk residue of broiler chicks originated from breeders of different ages and found that chicks from older breeders presented greater yolk weight.…”
Section: T (°C)supporting
confidence: 81%
“…The results of chick weight with or without yolk sac corroborate the findings of Rocha et al (2008) and Nangsuay et al (2013), who did not observe any influence of age of broiler breeders on the weight of the yolk residue of one-day-old chicks. However, results differ from those obtained by Riccardi et al (2009), who studied the weight of the yolk residue of broiler chicks originated from breeders of different ages and found that chicks from older breeders presented greater yolk weight.…”
Section: T (°C)supporting
confidence: 81%
“…However, Nangsuay et al (2013), evaluating breeders of different ages (29 and 53 weeks) and similar egg weights, did not find any differences in yolk-free chick weight. The yolkfree chick weight results obtained in the present study support the theory of Sklan et al (2003) that heavier eggs produce heavier chicks.…”
Section: Resultsmentioning
confidence: 99%
“…Late embryonic mortality was highest at 43 and 48 weeks of age. Embryos derived from old flock eggs produce more heat from d16 of incubation onwards than those of younger flock eggs (Nangsuay et al., ), and consequently, larger eggs (from older flocks) are at more risk for late term mortality (Elibol and Brake, ). It has been shown that changes in embryonic heat production influence the obtained eggshell temperature (Meijerhof and Van Beek, ), which can affect hatchability and chick quality (French, ; Lourens et al., ).…”
Section: Discussionmentioning
confidence: 99%